North Korea and security cooperation in Northeast Asia - Kwak, Tae-Hwan 1938-; Joo, Seung-Hod 1959- (Rethinking Asia and international relations, 2014)
This book explores the domestic factors of the two Koreas and the four major powers that influence their security policies towards North Korea and Northeast Asia. This well thought out and consistently analysed volume has huge potential to frame the conversation on Northeast Asian relations in the coming years.